Trained Sensory Panel Evaluation of the Impact of Bone-In Versus Boneless Cuts on Beef Palatability - K. J. Farmer; E. S. Beyer; S. G. Davis; K. M. Harr; M. D. Chao; J. L. Vipham; M. D. Zumbaugh; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of this study was to determine palatability traits of beef cuts of differing bone status and quality grade. Study Description:Paired (n = 12 pairs; 24 total/cut/grade) boneless ribeye rolls, export ribs, and short loins were procured. Short loins were fabricated into boneless strip loins with corresponding bone-in tenderloins, or bone-in strip loins with boneless tenderloins. Post-aging, subprimals were fabricated into steaks that were randomly selected for further analysis. A total of 18 trained sensory panels were conducted at the Kansas State University Meat Science Sensory Lab to determine differences in palatability traits. Results:In totality, bone status had a minimal impact on palatability traits. Nonetheless, bone-in tenderloins and bone-in ribeyes were rated more flavorful (P<0.05) than boneless cuts from the same muscle. There were no beef (P>0.05) flavor intensity differences observed for bone-in and boneless strip steaks. Bone state had no effect (P>0.05) on initial juiciness, myofibrillar tenderness, overall tenderness, or Warner-Bratzler shear force (WBSF) for any cut. Bone-in strip loin samples were rated juicier (P<0.05) than tenderloins and boneless ribeye samples. Tenderloin samples were rated higher (P<0.05) for myofibrillar and overall tenderness than strip loin and ribeye steaks, which were which were rated similar (P>0.05) by trained panelists. Furthermore, there was no difference (P>0.05) in the WBSF values for strips and ribeyes, with tenderloin samples having the lowest (P<0.05) average peak force. Lastly, USDA Choice samples were rated higher (P<0.05) for all palatability traits and had lower (P<0.05) WBSF values than Select samples. The Bottom Line:A similar overall eating experience could be derived from a boneless or bone-in steak from the same cut and quality grade.
Keywords: bone state; beef palatability; tenderloin